Creative Painting Titled "Traces of Sufficiency" - Uttama, Prapaporn (Chophayom Journal, 2023)
A study on the creation of the painting titled traces of sufficiency has two objectives; 1) to study and analyze concepts of traces of sufficiency and 2) to create the painting titled traces of shapes of sufficiency. The results of the study revealed two aspects reflecting the concept and emotions regarding traces of sufficiency. The first part was the shapes that were created and inspired by agricultural works reflecting ways of lives of local people in the countryside. The second part was the senses of simplicity, contentment, interdependence between human and nature and between nature and nature. The analysis of the first part was the shapes from agricultural work which enables the creation of the painting using artistic shapes by combining symbolic shapes in 4 paintings. The paintings focus on emotions that related to concepts bringing mixed painting techniques such as wet acrylic coloring looking transparent like watercolor, thick textures coloring, embroidery to create lines like dotted-lines and thick lines, black pencil shadowing creating fade traces and underlining. The accomplishment of the creative paintings generates the unique pieces of art with aesthetics and appreciation of human. Moreover, the wisdom of living in sufficiency, contentment, simplicity creating impacts on the notion of audience who may transfer to develop their lives, improve mind and perspectives in the way as the aim of the researcher. Keywords: Creative Paintings, Shapes, Sufficiency